Relationships between cerebral small vessel diseases markers and cognitive performance in stroke-free patients with atrial fibrillation - Tao, Wendan; Liu, Junfeng; Ye, Chen; Kwapong, William Robert; Wang, Anmo; Wang, Zhetao; Chen, Shi; Liu, Ming (Frontiers in Aging Neuroscience, 2023)
Background: Atrial fibrillation (AF) is related to an increased risk of cognitive dysfunction. Besides clinical stroke, AF can damage the brain via several pathophysiological mechanisms. We aimed to assess the potential mediating role of cerebral small vessel disease (SVD) in cognitive performance in individuals with AF. Methods: Stroke-free individuals with AF from the cardiological out-patients clinic at West China Hospital of Sichuan University were recruited. Extensive neuropsychological testing tools were assessed including global function, domains of attention, executive functions, learning and memory. 3T magnetic resonance imaging (MRI) was used for SVD markers assessment of white matter hyperintensities (WMH), lacunes, cerebral microbleeds (CMBs), and enlarged perivascular spaces (EPVS). The correlation between SVD markers and cognitive measures was analyzed by multivariate linear regression models. Results: We finally enrolled 158 participants, of whom 95 (60.1%) were males. In multivariate models, the presence of lacunes was independently associated with Montreal Cognitive Assessment (MoCA) (Model 1:ß=0.52, Model 2:ß=0.55), Rey Auditory Verbal Learning Test (RAVLT)-immediate and delayed recall (Model 1:ß=0.49; ß=0.69; Model 2:ß=0.53; ß=0.73) as well as Stroop-Acorrect (Model 1:ß=0.12; Model 2:ß=0.13), while total WMH severity independently associated with Strooptime-A (Model 1: ß=0.24; Model 3: ß=0.27), Strooptime-B (Model 1: ß=0.17; Model 3: ß=0.17), Strooptime-C (Model 1:ß=0.22; Model 3: ß=0.21) and Shape Trail Test (STT)-A (Model 1: ß=0.17; Model 3: ß=0.16). Conclusions: In our cohort of stroke-free individuals with AF, lacunes, and WMHs resulted as independently associated with cognitive decline while EPVS and CMBs did not show significance. Assessment of SVD MRI markers might be valuable for cognition risk stratification and facilitate optimal management of patients with AF.